Accelerated phosphorus removal using sulfate-coated expanded vermiculite - Taeyoon Lee (Water SA, 2020)
This study evaluated whether phosphorus in an aqueous solution can be effectively adsorbed and removed by sulfuric acid (SA)-coated vermiculite (SCV), which was synthetized by heating a mixture of expanded vermiculite (EV) and SA at 300°C. Phosphorus was removed from the aqueous solution and removal characteristics were evaluated by batch kinetic, batch adsorption, and column tests. The phosphate removal rates (h-1) for 1, 2.5, 5, 7.5, 12.5, and 25 g∙L-1 of SCV were 0.00015, 0.0011, 0.0044, 0.0087, 0.0648, and 0.5002, respectively. The Qmax of the Langmuir model and the partition coefficients of the linear and Freundlich models were 8.92 mg∙g-1, 0.65 L∙g-1, and 4.60 L∙g-1 (1/n = 0.354), respectively. The equilibrium phosphorus adsorptions (qe) were 7.47, 14.69, and 19.53 mg∙g-1 at initial concentrations of 10, 25, and 50 mg∙L-1, respectively. These results show that SCV can efficiently adsorb phosphorus in an aqueous solution.